DEVELOPMENT OF WATER LEVEL MONITORING APPLICATIONS IN SMART HOME SYSTEMS USING FLUTTER - Hendriawan, Muhammad; Haryono, Haryono; Budiman, Thomas (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Monitoring the water level at smart home system is an effort to increase the comfort and safety of its residents. Therefore, this study aims to design and develop a water level monitoring application that can be implemented to smart home system using the ESP8266 NodeMCU, HC-SR04 ultrasonic sensor, MQTT protocol, and the Flutter framework. By implementing Flutter as an open-source framework for creating applications, it can be monitor water levels in real-time accessed from various platforms: such as Android, iOS, Web, Windows, macOS, and Linux. The test expected to function correctly and provide accurate and real-time information regarding water levels in the surrounding area and can be accessed using various platforms. This research likely to be successful because previous studies conducted the same components in this study.